Quatre textes pazande - Degbe, Joseph; Grodya, Musafiri; Ntumba, Tshimanga; Pasch, Helma (AAeO - Afrikanistik-Aegyptologie-Online, 2019)
This publication of four texts is the first in a series that aims to give Zande speakers access to Turé’s stories and other Zande texts. To make the texts more appealing, they are presented in written form and also as audio files, which Joseph Degbe produced in March and April 2016 at the University of Kisangani. The glosses will aid in the analysis of morphosyntactic structures.